Characterization of Fusarium Diversity and Head Microbiota Associated with Rice Spikelet Rot Disease - Qun Cao; Jianyan Wu; Tianling Ma; Chengxin Mao; Chuanqing Zhang (Plants)
Rice spikelet rot disease (RSRD) affects the production and market price of rice, and can be harmful to humans and livestock. In this study, 51 strains of Fusarium spp. were isolated from rice spikelets in the Lin’an, Yuhang, and Fuyang regions. The isolates comprised four composite species: Fusarium incarnatum-equiseti species complex (FIESC), Fusarium asiaticum species complex (FSAMSC), Fusarium fujikuroi species complex (FFSC), Fusarium commune species complex (FNSC), and five species of Fusarium spp. (F. luffae, F. sulawesiense, F. asiaticum, F. fujikuroi, and F. commune). The separation rate of F. sulawesiense was the highest (41.2%), followed by F. asiaticum at 37.3%. The results of this study, compared with those of other studies, found that the newly discovered species of Fusarium spp. associated with RSRD were FSAMSC (F. asiaticum) and FNSC (F. commune). Temperature is one of the important factors causing RSRD; the optimal growth temperature for F. sulawesiense and F. commune was 30 °C, and the optimal growth temperature for other species was 25 °C. A high temperature of 35 °C did not inhibit the growth of Fusarium, as F. commune and F. fujikuroi could grow at this temperature. At 20–30 °C, the growth rate of F. asiaticum was higher than those of other strains. To determine whether the occurrence of RSRD is related to the correlation between Fusarium and other fungi in rice spikelets under different health conditions, the genetic diversity of fungi in rice spikelets was analyzed by amplicon Internal Transcribed Spacer (ITS) sequencing, and the correlations between strains of Fusarium spp. were measured. The results showed that the fungal diversity of diseased rice spikelets (RD) was higher than that of relatively healthy rice spikelets (RH). Curvularia spp., which was affected by the condition of the spikelets, was negatively correlated with Fusarium spp. in RH and positively correlated with Fusarium spp. in RD. Therefore, Fusarium spp. and Curvularia spp. can jointly cause the occurrence of RSRD. The results of the study are significant for understanding the occurrence of RSRD and formulating prevention and control measures.